If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 1 = -14 Reorder the terms: 1 + 3n = -14 Solving 1 + 3n = -14 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3n = -14 + -1 Combine like terms: 1 + -1 = 0 0 + 3n = -14 + -1 3n = -14 + -1 Combine like terms: -14 + -1 = -15 3n = -15 Divide each side by '3'. n = -5 Simplifying n = -5
| 10a-5+(a-3)=15 | | 1+8x=2x-3 | | 15y+-10+7=2(7y+-1)+-1y | | 15y+-10+3=2(3y+-1)+-1y | | (2ty)(-6t)= | | 15y+-10+1=2(1y+-1)+-1y | | 7+28m=42+21m | | 15y+-10+2=2(2y+-1)+-1y | | -9x+3+2x=-11 | | 15y+-10+1=2(ky+-1)+-1y | | 15y+-10+3=2(ky+-1)+-1y | | 3y+3x=45 | | 2r-5s=k | | -4x+5-2x+3= | | 15y+-10+6=2(ky+-1)+-1y | | X^2-11x=-56 | | (0)=-4.8x+1.2 | | (2.5b-9)+6b=-7 | | 8m-6=2 | | 5(a-1)=5 | | 5(3x+-2)=4+-6x | | 4(3x+-2)=4+-6x | | -11=7+b | | 4w+10=90 | | 43v-6=8+23v | | 12x+6=5y+10 | | 4w+10= | | 2x-3(3-7)+3= | | 3(3x+-2)=4+-6x | | Y=-4.8(0)+1.2 | | 2(3x+-2)=4+-6x | | 150m-125m+38200=40400-175m |